2000
DOI: 10.1111/j.1348-0421.2000.tb02520.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and Taxonomic Heterogeneity of Cryptococcus humicolus by Analysis of the Sequences of the Internal Transcribed Spacer Regions and 18S rDNA, and the Phylogenetic Relationships of C. humicolus, C. curvatus, and the Genus Trichosporon

Abstract: The phylogenetic and taxonomic heterogeneity of a rare opportunistic yeast pathogen, Cryptococcus humicolus, was revealed by analysis of the sequence of the internal transcribed spacer (ITS) region. Sixteen strains of C. humicolus showed a wide diversity in their ITS sequences. In addition, their 18S rDNA sequences were determined and used to analyze the phylogenetic relationships among C. humicolus and related yeasts. On trees constructed by the Neighbor-Joining and Maximum Parsimony methods, C. humicolus str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…ITS2 and ITS1 were better than 26S at resolving the taxonomic position of Cryptococcus humicolus. In agreement with our data, this species has been previously shown to belong to the Trichosporon clade by analysis of 18S rDNA and ITS sequences (29), as well as 26S rDNA (10). In the ascomycetous group, Pichia species were polyphyletic in all three dendrograms.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…ITS2 and ITS1 were better than 26S at resolving the taxonomic position of Cryptococcus humicolus. In agreement with our data, this species has been previously shown to belong to the Trichosporon clade by analysis of 18S rDNA and ITS sequences (29), as well as 26S rDNA (10). In the ascomycetous group, Pichia species were polyphyletic in all three dendrograms.…”
Section: Discussionsupporting
confidence: 80%
“…DNA-based methods have been used successfully to characterize pathogenic yeasts and provide evidence of novel species (1,2,5,7,10,12,14,25,(27)(28)(29)31). We have established an ITS database that provides accurate identification of at least 40 species of medically important yeasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These species, with the exception of C. curvata, are taxonomically highly heterogeneous. We have previously reported the intraspecies diversity of C. humicola and C. laurentii by sequence analyses of the 18S,28S, and internal transcribed spacer (ITS) regions of the rRNA gene (20,21). Recently, Fonseca et al (3) demonstrated the species heterogeneity of C. albidus by using 28S rONA and ITS region sequences.…”
mentioning
confidence: 99%
“…For further taxonomical analysis of strain TYC-19, the ITS sequences, which appears to be a powerful technique to differentiate between phylogenetically intimately related species 18) , were determined. These results revealed that the strains were divided into three groups and strain TYC-19 branched off independently from all strains (…”
Section: Resultsmentioning
confidence: 99%